N-terminal domain of prion protein directs its oligomeric association - Trevitt, Clare R.; Hosszu, Laszlo L.P.; Batchelor, Mark; Panico, Silvia; Terry, Cassandra; Nicoll, Andrew J.; Risse, Emmanuel; Taylor, William A.; Sandberg, Malin K.; Al-Doujaily, Huda; Linehan, Jacqueline M.; Saibil, Helen R.; et al. (American Society for Biochemistry and Molecular Biology, 2014)
The self-association of prion protein (PrP) is a critical step in the pathology of prion diseases. It is increasingly recognized that small non-fibrillar β-sheet-rich oligomers of PrP may be of crucial importance in the prion disease process. Here, we characterize the structure of a well defined β-sheet-rich oligomer, containing ∼12 PrP molecules, and often enclosing a central cavity, formed using full-length recombinant PrP. The N-terminal region of prion protein (residues 23-90) is required for the formation of this distinct oligomer; a truncated form comprising residues 91-231 forms a broad distribution of aggregated species. No infectivity or toxicity was found using cell and animal model systems. This study demonstrates that examination of the full repertoire of conformers and assembly states that can be accessed by PrP under specific experimental conditions should ideally be done using the full-length protein.